Implementación de un sistema de contabilidad de costos en la empresa florícola Spacium s.a. ubicada en la parroquia Mulalillo, cantón Salcedo, provincia de Cotopaxi, al periodo del 1 de agosto al 31 de diciembre del 2013 - Molina Tonato, Luis Alberto (2015)
At the present, for enterprises to have a good cost system is to possess a competitive advantage against other, since, it helps the management to better decision-making according with the principles and organization of the modern management. Therefore, is made the present thesis in order to implement a costs system based in activities in the Floriculture SPACIUM S.A., since knowing the real costs of the products; it is essential to define which activities are carried out into the enterprise, how many do they cost the same, why do they need to make them. Identifying relevant activities and assigning indirect costs to each activity in proportion to the resources use, identifying inducers of appropriate costs for each activity and assigning the indirect costs to products, the selves are an economic map of the costs and profitability in based to the activities, to achieve this aims testing all documents and information facilitated by the departments of the enterprise which provided the most precise information about the cost of the activities required to produce roses, accounting system of costs based on designed activities; it is generated according the needs of the enterprise which will allow to make decisions that optimatize developed activities in the productive processes as the activity-based system costing can identify the activities what create value and unnecessary costs, assisting as important point the resources optimization and profits increase and achieving business success.